Analysis of the fatigue crack growth mechanisms in equimolar body centered cubic HfNbTaTiZr high-entropy alloy: Discussions on its singularities and consequences on the crack propagation rate properties. (July 2019) - Guennec, B.; Kentheswaran, V.; Perrière, L.; Ueno, A.; Guillot, I.; Couzinié, J-Ph; Dirras, G.
Abstract: In the present work, the fatigue crack propagation mechanisms of the body centered cubic (BCC) equimolar HfNbTaTiZr HEA are investigated in air and at room temperature. A fatigue threshold Δ K th of 2.5 MPa m 1/2 coupled with a slope parameter of the Paris regime m of 2.2 at a stress ratio of 0.1 are reported. The fatigue threshold over elastic modulus ratio Δ K th / E corresponds approximately to the lower bound of the usual range reported for this value among the metallic materials. The fracture surfaces outlined crystallographic fatigue crack propagation mechanism, where the formation of striation patterns having spacing identical to crack propagation rate is noted. The crack path analysis emphasized a crack spreading along both {011} and {112} slip planes. This profusion of planes implies singularities of the crack propagation in comparison with other metallic materials prone to crystallographic crack propagation. Graphical abstract: Image 1 Highlights: Fatigue crack growth features of BCC HfNbTaTiZr HEA are investigated. A Paris regime is detected with a slope parameter of 2.2 from Δ K  = 5 MPa m 1/2 . Striation pattern on the fracture surfaces are correlated to crack growth velocity. Crack path is conveyed on both {011} and {112} planes. The fatigue threshold Δ K th  = 2.5 MPa m 1/2 induces a ratio Δ K th / E in the usual range.